Investments as a Factor of Sustainable Development of Rural Areas - KURMANOVA, Dana Sultankhanovna; ISMAILOVA, Aliya Sabirzhanovna; UKIBAYEVA, Gulim Kabikenovna; ABDILDINOVA, Nailya Ermukhanovna; BAKYEI, Agipar (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
Sustainable development of agriculture depends heavily on the efficient utilization of all production factors, such as a reinforcement of physical infrastructure, application of science and technology, industry investment, and innovations. Agriculture plays a key role in the Kazakh economy and its sustainable development defines the country’s economic and political position. Therefore, agriculture has a complex strategic value, and activation of investments and innovations is a defining factor for the sustainable development of agriculture. The purpose of the study is to research the investment as a source and develop proposals to increase the investment for the sustainability of agriculture. The "Data Analysis” package was used for the study in a combination with methods of logical and statistical analysis. The calculations show that the combined impact of factors leads to an increased capacity for sustainable development of rural areas. The expected research results may vary and depend on the stakeholders’ interests. The proposed model will contribute to investment attractiveness, reinforcement of the investment activity and practical investment to agriculture, a high-quality design of investment projects, and personal interest of each agricultural producer in the results of their actions. Altogether, this will provide a significant increase in the economic efficiency of the industry.